2002
DOI: 10.1080/10446670310001593497
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the IDDM Candidate Gene Prss16 in NOD and NON Mice

Abstract: The thymus-specific serine protease Prss16 is highly expressed by the epithelial cells in the thymic cortex. It has been suggested to play an important role in the positive selection of T cells through the antigen presention pathway of the cortical antigen presenting cells. Recently, the gene ecoding Prss16 has been linked to insulin dependent diabetes mellitus (IDDM) susceptibility independent of HLA-DR3 suggesting the Prss16 may be involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Published in situ hybridization studies showed that Tssp is predominantly expressed by cTECs but not to significant levels in the hematopoietic compartment (8,9,22). In agreement, we found very high levels of Prss16 mRNA in cTECs but not in medullary TECs.…”
Section: Figuresupporting
confidence: 78%
See 1 more Smart Citation
“…Published in situ hybridization studies showed that Tssp is predominantly expressed by cTECs but not to significant levels in the hematopoietic compartment (8,9,22). In agreement, we found very high levels of Prss16 mRNA in cTECs but not in medullary TECs.…”
Section: Figuresupporting
confidence: 78%
“…Mice were immunized with the corresponding Ag in CFA, and their recall response was analyzed in vitro. Quite unexpectedly in light of the foremost role of insulin in diabetes development (31,32), we found that the frequency of IL-2-producing CD4 T cells specific for Ins [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and Ins [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] was comparable in Tssp° and WT NOD mice ( Figure 6). Likewise WT and Tssp° NOD mice responded similarly to the GAD 206-220 peptide and the known IGRP immunodominant epitopes ( Figure 6).…”
Section: Figurementioning
confidence: 96%
“…We next examined whether TSSP deficiency may likewise impact on the generation of a polyclonal HEL-specific CD4 T cell repertoire using BM chimeras. TSSP is highly expressed by cTEC (Bowlus et al, 1999;Carrier et al, 1999;Cheunsuk et al, 2002) but also, at lower levels, by thymic DCs (unpublished data). Therefore, we examined the effect of TSSP deficiency in radioresistant TECs on the differentiation of some HEL-specific CD4 T cells by injecting WT BM cells into lethally irradiated Tssp / NOD-C° mice (WT → KO) or, as control, into NOD-C° host (WT → WT).…”
Section: Distinct Tcr Repertoire Features Of Hel-responsive Cd4 T Cells From Tssp / Micementioning
confidence: 98%